Expert estimation of the processes in ergatic teaching system - Шибицкий, В. П. (Proceedings of National Aviation University (archive), 2000)
Proposed is a method of expert estimation of processes in slightly formalized information teaching medium on the basis of a structural model of didactic knowledge and test indicators in logical-semantic basis